Substance Use and Barriers to Treatment Across Native Hawaiians/Pacific Islanders and Asian Americans - Levine, Lauren Michelle (2008)
Research shows that Asian Americans have lower rates of substance abuse treatment utilization than Caucasians. However, investigators have recently begun to separate Native Hawaiians/Pacific Islanders (NH/PI) from Asian Americans. Thus, it remains unclear whether disparities in barriers to treatment utilization differ across NH/Pis and Asian Americans. Data (N = 43,093) from the 2001-2002 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a large, nationally representative survey was used in this study. A chi-square analysis examined whether disparities in barriers and utilization differed between NH/Pis (n = 300) and Asian Americans (n = 1,334). We found that NH/Pis who thought they should seek treatment for their drinking were statistically and significantly less likely than Asian Americans to do so. We found no statistically significant differences for drug use. We also found that NH/Pis were more likely to meet criteria for a substance use disorder than Asian Americans. Results suggest the possibility that alcohol use has become increasingly embedded and normalized in NH/PI culture as opposed to Asian American culture while drug use has not. Thus, alcohol's normalization may result in NH/Pis more frequently failing to seek needed alcohol treatment. This indicates that public health policy should consider alcohol and drug use separately when designing and implementing culturally-specific preventions and interventions and focus on the de-normalization of alcohol use. Large-scale surveys of NH/Pis are needed to better identify barriers to treatment and utilization patterns. In sum, results highlight the need to increasingly consider cross-cultural variation in research while simultaneously developing culturally sensitive prevention and intervention programs